The Use of Natural Disaster Picture as a Medium of Learning to Write Report Text - Ayu Setiya Ningsih; Sayit Abdul Karim (Universitas Muhammadiyah Kalimantan Timur, 2023)
Writing is one of the language skills that is considered difficult for most Indonesian EFL students. Teachers are challenged to provide an interesting medium of learning to increase students' writing skills and motivation. Natural disaster pictures can be utilized as an alternative medium for learning to write report text. Therefore, this study aims to find out students' ability in writing report texts using natural disaster picture and to describe perceptions of students in using natural disaster picture as a medium of learning to write report texts. The respondents were 22 students in the tenth grade at SMA N 1 Binangun in the academic year 2021/2022. A descriptive quantitative study was utilized in the present study. To collect the data needed, the researchers used tests and questionnaires. Furthermore, a test is used to collect the data on students' achievement in writing report text, meanwhile, a questionnaire is used to find out students' perceptions of using natural disaster picture as a learning medium to write report text. The results of the study revealed that the total score of students is 1308 and the mean score is 60. It means that the achievement of tenth-grade students at SMA N 1 Binangun is categorized as